Effect of systematic ergonomic hazard identification and control implementation on musculoskeletal disorder and injury risk - Linda F Cantley; Oyebode A Taiwo; Deron Galusha; Russell Barbour; Martin D Slade; Baylah Tessier-Sherman; Mark R Cullen (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: This study aimed to examine the effect of an ergonomic hazard control (HC) initiative, undertaken as part of a company ergonomics standard, on worker injury risk. METHODS: Using the company's ergonomic hazards database to identify jobs with and without ergonomic HC implementation and linking to individual job and injury histories, injury risk among person-jobs with HC implementation (the HC group) was compared to those without HC (NoHC group) using random coefficient models. Further analysis of the HC group was conducted to determine the effect of additional ergonomic hazards controlled on injury risk. RESULTS: Among 123 jobs at 17 plant locations, 347 ergonomic hazards were quantitatively identified during the study period. HC were implemented for 204 quantified ergonomic hazards in 84 jobs, impacting 10 385 persons (12 967 person-jobs). No HC were implemented for quantified ergonomic hazards in the remaining 39 jobs affecting 4155 persons (5046 person-jobs). Adjusting for age, sex, plant origin, and year to control for any temporal trend in injury risk, the relative risk (RR) for musculoskeletal disorder (MSD) was 0.85 and the RR for any injury or MSD was 0.92 in the HC compared to NoHC group. Among the HC group, each ergonomic hazard controlled was associated with risk reduction for MSD and acute injury outcomes (RR 0.93). CONCLUSION: Systematic ergonomic HC through participatory ergonomics, as part of a mandatory company ergonomics standard, is associated with MSD and injury risk reduction among workers in jobs with HC implemented.